Pengaruh Profitabilitas, Leverage, dan Kepemilikan Institusional Terhadap Konservatisme Akuntansi: Studi Empiris pada Perusahaan Non Keuangan Sektor Basic Materials di BEI Periode 2021-2023 - Rahmad Galih Aditya; Nursiam (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Accounting conservatism is a principle of prudence in the preparation of financial statements.This study aims to obtain empirical evidence regarding the influence of profitability, leverage, and institutional ownership on accounting conservatism in companies in the Basic Materials Sector listed on the Indonesia Stock Exchange during the 2021–2023 period. The independent variables in this study are profitability, leverage, and institutional ownership, while the dependent variable is accounting conservatism. The sampling technique used is purposive sampling. A total of 101 companies met the criteria as observation units. The analytical method used is multiple linear regression analysis, which has passed the classical assumption tests. The results of this study provide empirical evidence that profitability has a significant effect on accounting conservatism. Leverage has an insignificant effect, while institutional ownership has no effect on accounting conservatism. The application of the conservatism principle in the presentation of financial statements allows stakeholders such as investors, creditors, and other external parties to reduce information asymmetry and obtain more realistic and useful information.